1995
DOI: 10.1248/cpb.43.1598
|View full text |Cite
|
Sign up to set email alerts
|

Improved Total Synthesis and Structure-Activity Relationship of Arenastatin A, a Potent Cytotoxic Spongean Depsipeptide.

Abstract: An efficient asymmetric synthesis of a cyclic depsipeptide arenastatis A (1) is described. 1, isolated from the marine sponge Dysidea arenaria, exhibited extremely potent cytotoxicity with IC50 of pg/ml for KB cells, and in this context the structure-activity relationship among several stereoisomers of 1 and allied compounds has also been examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 0 publications
0
41
0
Order By: Relevance
“…Depending on this, different strategies for dealing with the stereochemical issue have been developed. Thus, the anti stereochemistry can be set by epoxide opening, [11Ϫ13] by a syn aldol reaction followed by reduction of the carboxylate to a methyl group, [14,15] by crotylboration of an aldehyde, [16,17] by nucleophilic addition to a 2-methyl aldehyde, [18] by Frater alkylation of a 3-hydroxy ester, [17] or by a [2,3]-Wittig rearrangement. [19] If a diol precursor such as II is targeted, aldol strategies [20] or nucleophilic additions to the aldehyde derived from man-delate are possible.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on this, different strategies for dealing with the stereochemical issue have been developed. Thus, the anti stereochemistry can be set by epoxide opening, [11Ϫ13] by a syn aldol reaction followed by reduction of the carboxylate to a methyl group, [14,15] by crotylboration of an aldehyde, [16,17] by nucleophilic addition to a 2-methyl aldehyde, [18] by Frater alkylation of a 3-hydroxy ester, [17] or by a [2,3]-Wittig rearrangement. [19] If a diol precursor such as II is targeted, aldol strategies [20] or nucleophilic additions to the aldehyde derived from man-delate are possible.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous syntheses of both the arenastatins and cryptophycins have been published, 1,6,20 " 23 the epoxidation step has always 24 been done using m-CPBA or dimethyldioxirane. This is of significance because the two diastereomers formed, at best in a 2:1 ratio of ß:oc epoxides, cannot generally be separated by column chromatography.…”
Section: Epoxidation Studiesmentioning
confidence: 99%
“…A close structural relative of the cryptophycins, Arenastatin A (3), was isolated from the Okinawan marine sponge Dysidea arenaria. 6 Arenastatin A differs from Cryptophycin A in that it lacks both the chlorine on the aryl ring at CIO and the methyl group at C6. 6 Microtubules are dynamic components and are essential to cellular life.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Formal and total syntheses of the cryptophycins have been published by several groups. [8][9][10][11][12][13][14] Also, a multitude of SAR studies of these molecules have been reported. 2 ' 3 " ,16 or Arenastatin A Although relatively little is known about the interactions of cryptophycins with tubulin, it is believed that the cryptophycins may interact in a manner different from those of other tubulin-binding antimitotic agents.…”
Section: Introductionmentioning
confidence: 99%